Mycoplasma hyopneumoniae resides intracellularly within porcine epithelial cells - Raymond, B. B. A. (Sci Rep, 2018)
Enzootic pneumonia incurs major economic losses to pork production globally. The primary pathogen and causative agent, Mycoplasma hyopneumoniae, colonises ciliated epithelium and disrupts mucociliary function predisposing the upper respiratory tract to secondary pathogens. Alleviation of disease is reliant on antibiotics, vaccination, and sound animal husbandry, but none are effective at eliminating M. hyopneumoniae from large production systems. Sustainable pork production systems strive to lower reliance on antibiotics but lack of a detailed understanding of the pathobiology of M. hyopneumoniae has curtailed efforts to develop effective mitigation strategies. M. hyopneumoniae is considered an extracellular pathogen. Here we show that M. hyopneumoniae associates with integrin β1 on the surface of epithelial cells via interactions with surface-bound fibronectin and initiates signalling events that stimulate pathogen uptake into clathrin-coated vesicles (CCVs) and caveosomes. These early events allow M. hyopneumoniae to exploit an intracellular lifestyle by commandeering the endosomal pathway. Specifically, we show: (i) using a modified gentamicin protection assay that approximately 8% of M. hyopneumoniae cells reside intracellularly; (ii) integrin β1 expression specifically co-localises with the deposition of fibronectin precisely where M. hyopneumoniae cells assemble extracellularly; (iii) anti-integrin β1 antibodies block entry of M. hyopneumoniae into porcine cells; and (iv) M. hyopneumoniae survives phagolysosomal fusion, and resides within recycling endosomes that are trafficked to the cell membrane. Our data creates a paradigm shift by challenging the long-held view that M. hyopneumoniae is a strict extracellular pathogen and calls for in vivo studies to determine if M. hyopneumoniae can traffic to extrapulmonary sites in commercially-reared pigs.